Behavioural intervention to reduce sexually transmitted infections in people aged 16-24 years in the UK: the safetxt RCT - Caroline Free; Melissa J Palmer; Kimberley Potter; Ona L McCarthy; Lauren Jerome; Sima Berendes; Anasztazia Gubijev; Megan Knight; Zahra Jamal; Farandeep Dhaliwal; James R Carpenter; Tim P Morris; et al. (NIHR Journals Library, 2023)
Background: The prevalence of genital chlamydia and gonorrhoea is higher in the 16-24 years age group than those in other age group. With users, we developed the theory-based safetxt intervention to reduce sexually transmitted infections. Objectives: To establish the effect of the safetxt intervention on the incidence of chlamydia/gonorrhoea infection at 1  year. Design: A parallel-group, individual-level, randomised superiority trial in which care providers and outcome assessors were blinded to allocation. Setting: Recruitment was from 92 UK sexual health clinics. Participants: Inclusion criteria were a positive chlamydia or gonorrhoea test result, diagnosis of non-specific urethritis or treatment started for chlamydia/gonorrhoea/non-specific urethritis in the last 2 weeks; owning a personal mobile phone; and being aged 16-24 years. Allocation: Remote computer-based randomisation with an automated link to the messaging system delivering intervention or control group messages. Intervention: The safetxt intervention was designed to reduce sexually transmitted infection by increasing partner notification, condom use and sexually transmitted infection testing before sex with new partners. It employed educational, enabling and incentivising content delivered by 42-79 text messages over 1 year, tailored according to type of infection, gender and sexuality. Comparator: A monthly message regarding trial participation. Main outcomes: The primary outcome was the incidence of chlamydia and gonorrhoea infection at 12 months, assessed using nucleic acid amplification tests. Secondary outcomes at 1 and 12 months included self-reported partner notification, condom use and sexually transmitted infection testing prior to sex with new partner(s). Results: Between 1 April 2016 and 23 November 2018, we assessed 20,476 people for eligibility and consented and randomised 6248 participants, allocating 3123 to the safetxt intervention and 3125 to the control. Primary outcome data were available for 4675 (74.8%) participants. The incidence of chlamydia/gonorrhoea infection was 22.2% (693/3123) in the intervention group and 20.3% (633/3125) in the control group (odds ratio 1.13, 95% confidence interval 0.98 to 1.31). There was no evidence of heterogeneity in any of the prespecified subgroups. Partner notification was 85.6% in the intervention group and 84.0% in the control group (odds ratio 1.14, 95% confidence interval 0.99 to 1.33). At 12 months, condom use at last sex was 33.8% in the intervention group and 31.2% in the control group (odds ratio 1.14, 95% confidence interval 1.01 to 1.28) and condom use at first sex with most recent new partner was 54.4% in the intervention group and 48.7% in the control group (odds ratio 1.27, 95% confidence interval 1.11 to 1.45). Testing before sex with a new partner was 39.5% in the intervention group and 40.9% in the control group (odds ratio 0.95, 95% confidence interval 0.82 to 1.10). Having two or more partners since joining the trial was 56.9% in the intervention group and 54.8% in the control group (odds ratio 1.11, 95% confidence interval 1.00 to 1.24) and having sex with someone new since joining the trial was 69.7% in the intervention group and 67.4% in the control group (odds ratio 1.13, 95% confidence interval 1.00 to 1.28). There were no differences in safety outcomes. Additional sensitivity and per-protocol analyses showed similar results. Limitations: Our understanding of the mechanism of action for the unanticipated effects is limited. Conclusions: The safetxt intervention did not reduce chlamydia and gonorrhoea infections, with slightly more infections in the intervention group. The intervention increased condom use but also increased the number of partners and new partners. Randomised controlled trials are essential for evaluating health communication interventions, which can have unanticipated effects. Future work: Randomised controlled trials evaluating novel interventions in this complex area are needed. Trial registration: This trial is registered as ISRCTN64390461. Funding: This project was funded by the National Institute for Health and Care Research (NIHR) Public Health Research programme and will be published in full in Public Health Research; Vol. 11, No. 1. See the NIHR Journals Library website for further project information.